2010
DOI: 10.1136/pgmj.2009.096446
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of the role of ‘mindbody’ factors in chronic urticaria

Abstract: Chronic spontaneous urticaria (CSU) is a very common skin condition that causes considerable suffering and is often poorly responsive to drug treatment regimens. Most clinicians accept that multiple factors play a role in the aetiology of CSU, but there is a widespread reluctance to accept a significant role for 'mindbody' factors, despite a large number of clinical reports and studies over many decades suggesting their relevance. This reluctance has multiple origins. A primary influence is the flawed dualisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…Further, the biomedical approach is dualistic and views emotional factors and physical manifestations of disease as separate entities. The standard approach to CSU treatment is no different even though literature suggests an important role of stress and emotional factors in CSU …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the biomedical approach is dualistic and views emotional factors and physical manifestations of disease as separate entities. The standard approach to CSU treatment is no different even though literature suggests an important role of stress and emotional factors in CSU …”
Section: Discussionmentioning
confidence: 99%
“…The standard approach to CSU treatment is no different even though literature suggests an important role of stress and emotional factors in CSU. [36][37][38][39] A pilot study 40 Knowledge regarding the prevalence and etiology and disease management and therapy response in CSU among children and adolescents is scarce. 41 Gathering information regarding prevalence might best be done with school-based programs, as most CSU cases in childhood never reach specialists but are managed by general practitioners and from home.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing a patient's urticaria purely from the perspective of their clinical symptoms ignores a large and important part of their disease experience. Over the past century, a succession of reports has suggested a role for emotions and stress in initiating and perpetuating urticaria . Recent psychoneuro‐immunology research points to a significant influence of the ‘mind‐brain complex’ on the immune system.…”
Section: Treating the Urticaria Patient As A Wholementioning
confidence: 99%
“…[20,16] This local lesion may be affected by nervous system as there is an organic and functional relation between mast cells and peripheral nervous system. [21] CONCLUSION Findings of the current study conclude that psychological disorders are found as co morbidity in chronic urticaria patients. Therefore, Psychiatrist assistance is unavoidable for the patients suffering with chronic urticaria to avoid as well as treatment of psychological disorders.…”
Section: Discussionmentioning
confidence: 65%